Biomechanical behavior of bone scaffolds made of additive manufactured tricalciumphosphate and titanium alloy under different loading conditions - Wieding, Jan; Fritsche, Andreas; Heinl, Peter; Körner, Carolin; Matthias, Cornelsen; Seitz, Hermann; Mittelmeier, Wolfram; Bader, Rainer (Journal of Applied Biomaterials and Fundamental Materials, 2013)
Purpose: The repair of large segmental bone defects caused by fracture, tumor or infection remains challenging in orthopedic surgery. The capability of two different bone scaffold materials, sintered tricalciumphosphate and a titanium alloy (Ti6Al4V), were determined by mechanical and biomechanical testing. Methods: All scaffolds were fabricated by means of additive manufacturing techniques with identical design and controlled pore geometry. Small-sized sintered TCP scaffolds (10 mm diameter, 21 mm length) were fabricated as dense and openporous samples and tested in an axial loading procedure. Material properties for titanium alloy were determined by using both tensile (dense) and compressive test samples (open-porous). Furthermore, large-sized open-porous TCP and titanium alloy scaffolds (30 mm in height and diameter, 700 μm pore size) were tested in a biomechanical setup simulating a large segmental bone defect using a composite femur stabilized with an osteosynthesis plate. Static physiologic loads (1.9 kN) were applied within these tests. Results: Ultimate compressive strength of the TCP samples was 11.2 ± 0.7 MPa and 2.2 ± 0.3 MPa, respectively, for the dense and the open-porous samples. Tensile strength and ultimate compressive strength was 909.8 ± 4.9 MPa and 183.3 ± 3.7 MPa, respectively, for the dense and the open-porous titanium alloy samples. Furthermore, the biomechanical results showed good mechanical stability for the titanium alloy scaffolds. TCP scaffolds failed at 30% of the maximum load. Conclusions: Based on recent data, the 3D printed TCP scaffolds tested cannot currently be recommended for high loadbearing situations. Scaffolds made of titanium could be optimized by adapting the biomechanical requirements. © 2013 Società Italiana Biomateriali.
Keywords: Bone scaffolds; Large segmental bone defects; Mechanical properties; Sintered tricalciumphosphate; Static loading; Titanium